2022
DOI: 10.35848/1347-4065/ac95e7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrostatic pressure on mechanical and optoelectronic properties of ACuO3 (A = Ca, Sr)

Abstract: We investigate the hydrostatic pressure dependences of elastic, electronic, and optical properties of newly hypothesized perovskite compound ACuO3 (A=Ca, Sr) using the first-principles method. The structural and mechanical stabilities have been established theoretically under pressure up to 100 GPa. The ductile nature of these transition metal oxides have been confirmed by the calculation of elastic constants. The relatively low value of Young modulus possesses high thermal shock resistance and proclaims the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Figure 1 a shows the 3D and 2D schematic illustration of cubic CNO crystal structure. By fitting the reduced total energy of the crystal with respect to the volume of the unit cell using the Birch–Murnaghan equation of state 15 , the geometry optimizations were carried out to find the lattice constants, isothermal bulk moduli, and pressure derivatives. The obtained value of a = 4.15 Å, which is very close to the reported data of CNO 17 that asserts the authenticity of the present calculation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 a shows the 3D and 2D schematic illustration of cubic CNO crystal structure. By fitting the reduced total energy of the crystal with respect to the volume of the unit cell using the Birch–Murnaghan equation of state 15 , the geometry optimizations were carried out to find the lattice constants, isothermal bulk moduli, and pressure derivatives. The obtained value of a = 4.15 Å, which is very close to the reported data of CNO 17 that asserts the authenticity of the present calculation.…”
Section: Resultsmentioning
confidence: 99%
“…A number of theoretical and experimental research have been done to look at the different characteristics of perovskite systems such as niobates, titanates, cuprates, etc. Very recently, pressure-dependent theoretical investigations on mechanical, electronic, and optical properties of BaCuO 3 14 , CaCuO 3 and SrCuO 3 15 have been explored which shows their utility for several optoelectronic applications. The improvement of visible light driven photocatalytic activity and the expansion of light response ranges should therefore be the main research areas for oxide photocatalysts 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A smooth and computation-friendly pseudopotential was produced based on ultrasoft Vanderbilt-type pseudopotentials, and it saves computation time significantly without affecting the accuracy appreciably. The independent elastic constants and elastic moduli were calculated using the stress-strain method using the CASTEP code [47]. For a cubic system, the elastic moduli, Y, B, G, and Poisson's ratio, ν, were determined using the calculated elastic stiffness constants, Cij.…”
Section: First-principles Calculation Of Poisson's Ratio Of Crystalsmentioning
confidence: 99%
“…[ 18–20 ] The recent study on CaCuO 3 and SrCuO 3 has shown that hydrostatic pressure affects their elastic, electrical, and optical properties, making them important for a wide range of optoelectronic applications. [ 21 ] The transition from the initial state of Cu (2 p 6 3 d 9 ) to the final state of Cu (2 p 5 3 d 10 ) was observed under hydrostatic pressure. [ 22 ] The ionic and atomic radius of Sc atom is the highest in the first transition series.…”
Section: Introductionmentioning
confidence: 99%